Florid vulvar warts in a 39-year-old human immunodeficiency virus-positive woman: A case report - Rasheed, Fatima Abubakar; Usman, Asma'u; Abdurrahman, Aisha; Aliyu, Umar Usman; Yakasai, Ibrahim (Indian Journal of Case Reports, 2024)
Condyloma acuminata are human papillomavirus (HPV) infections frequently caused by HPV serotypes 6 and 11 that affect both sexes and are particularly infectious, recurrent, and negatively impact the quality of life of affected individuals. It is linked with the human immunodeficiency virus (HIV), is usually more aggressive and florid, and occurs at multiple sites with prevailing treatment difficulties in HIV-positive individuals. We present a curious case of florid vulvar warts in a 39-year-old HIV-positive woman.